Criação, implementação e validação de um repositório digital para podcast educativo - Saidelles, Tiago (2020)
The research aims to present the process of creating, implementing and validation of Digital Repository for Educational Podcast Storage, focusing on the different educational segments. Initially, research work on the application of the Podcast as an educational resource was developed, as well as the advantages, possibilities and challenges of its creation, listing the main publications related to the use of the Podcast, which points to the lack of studies related to this theme, corroborating the importance of this research. During the second phase, a study was carried out on the repositories maintained by the Ministry of Education, MEC: the International Bank for Educational Objects (BIOE), the Teacher Portal, the Virtual Interactive Education Network (RIVED) and the Public Domain, with In order to list the main advantages, problems and the main challenges that users encounter when using these platforms, the analysis of the repositories was based on the evaluation criteria used by Botton 2019, related to metadata, institutionalization, users, visibility and policies. Finally, based on the work developed so far, and after analysing the platforms, we proceeded to the proposal and implementation of a prototype of a digital repository for educational Podcast storage, considering that most of the Podcast production are dispersed in Network, not being shared among its audiences. In this perspective, digital repositories appear as an option to remedy this deficiency, concentrating these resources in just one database, enabling the consumer audience to have a faster and safer way to find these contents, thus enhancing their use and sharing. As a methodological approach, the research is based on Design-Based Research (DBR), as this methodology is used in research and application development in various areas, more specifically for the development of cognitive process proposals in digital educational environments. The preliminary results showed how much the studied repositories present inconsistency in their search methods, as well as a lack of specific guidelines regarding their metadata and indexing of the objects submitted to the repositories. It was also identified the lack of motivational initiatives for material deposits, as well as few opportunities for interaction between users. However, considering these difficulties identified during analysis, it is necessary to create a specific repository for Podcast, where users have ease, both in finding these resources in an accessible and reliable way, as well as a well-structured submission environment, enabling the use of these resources in educational environments making the construction of knowledge more active.